2010
DOI: 10.1001/archophthalmol.2009.354
|View full text |Cite|
|
Sign up to set email alerts
|

Outbreak of Acquired Ocular Toxoplasmosis Involving 248 Patients

Abstract: To describe the demographic profile and clinical and laboratory findings of 248 patients with acquired retinitis caused by systemic infection with toxoplasmosis in a presumed outbreak of the disease. Design: Retrospective observational case series. Results: Most patients (209) were residents of one city in Southern India. A total of 35 patients had a prodrome of fever, and 242 patients had unilateral retinitis without associated old retinochoroidal scars. All had laboratory evidence of acquired systemic infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 21 publications
4
54
0
4
Order By: Relevance
“…The 1.7% of cataract was similar to the findings of Balasundaram et al 30 and Tugal-Tutkun et al, 26 but considerably lower than the 13% reported by Bosch-Driessen et al; 5 the comparatively high rate of complications in the latter series is presumably due to the longer follow-up. Interestingly, although raised IOP is often associated with an OT episode 23,29,30 glaucoma as a complication is rare; that is, in the study of TugalTutkun et al, although an IOP rise was seen in 8% patients during active OT, there was no case of glaucoma as a complication, 26 nor was it seen in the series of Balasundaram et al 30 In our series, one case was complicated by glaucoma secondary to OT.…”
Section: Eyesupporting
confidence: 78%
See 1 more Smart Citation
“…The 1.7% of cataract was similar to the findings of Balasundaram et al 30 and Tugal-Tutkun et al, 26 but considerably lower than the 13% reported by Bosch-Driessen et al; 5 the comparatively high rate of complications in the latter series is presumably due to the longer follow-up. Interestingly, although raised IOP is often associated with an OT episode 23,29,30 glaucoma as a complication is rare; that is, in the study of TugalTutkun et al, although an IOP rise was seen in 8% patients during active OT, there was no case of glaucoma as a complication, 26 nor was it seen in the series of Balasundaram et al 30 In our series, one case was complicated by glaucoma secondary to OT.…”
Section: Eyesupporting
confidence: 78%
“…22,26 However, the rate of vitritis was lower than generally reported, 22,26,29,30 which may suggest that the level of vitreous haze was not always reliably recorded, particularly if low.…”
Section: Eyementioning
confidence: 82%
“…They are not killed by chemical and physical treatments currently applied in water treatment plants, including chlorination and ozone treatment (111). Outbreaks associated with the contamination of reservoirs supplying water, such as those described for the Greater Victoria area of British Columbia, Canada (16); in Santa Isabel do Ivai, Brazil (76); or in Coimbatore, India (21), involved a large number of patients. The epidemics were preceded by peaks of heavy rainfall and turbidity in the implicated reservoirs.…”
Section: Infection Through Oocystsmentioning
confidence: 99%
“…In India, Balasundaram et al (2010) described ocular involvement due to toxoplasmosis in 248 patients who had active retinochoroiditis and toxoplasmic serology suggesting recently acquired disease. Delair et al (2008) analysed 425 cases of ocular toxoplasmosis, 100 (23.5 %) were acquired, 62 (14.6 %) were congenital, and 263 (61.9 %) were of unknown origin.…”
Section: Parasitic Zoonoses In Europementioning
confidence: 99%